Strategic Plan in Improving the Quality Of Educators at SDN Banjarrejo, Belitang Jaya District, East Oku Regency - Iza Meidistina; Alhadi Yan Putra; Meilia Rosani (International Journal of Educational Technology and Society, 2025)
The purpose of this study was to determine the strategic plan in improving the quality of educators at SDN Banjarrejo, Belitang Jaya District, OKU Timur Re- gency. The research method used is a qualitative descriptive approach. Data were obtained through observation, interviews and documentation. The object of research is the principal, educators and school administration. Data were ana- lyzed by data reduction, data presentation and conclusion drawing. The results showed that the strategic plan in improving the quality of educators has been implemented well consisting of the main steps, namely; strategic plan, implemen- tation of strategic plans, and evaluation of strategic plans. The principal carried out a number of procedures, namely holding meetings and initiating, examining various laws and school policies, formulating a vision of a successful school future, analyzing the school internally and externally using SWOT analysis, identi- fying strategic issues, developing problem handling techniques, and evaluating and assessing activities that need to be improved.